"It's just like a break-up": A qualitative analysis of turning points in female friendships in early to middle adulthood. Issue 1 (1st January 2021) - Doherty, Eileen F.
ABSTRACT: Considerable research has examined turning points within romantic relationships, but studies exploring turning points in the context of friendship are relatively scarce and focus mainly on friendships among college students. Friendships between women during the post-college years through middle-age have received scant attention. Utilizing an adaptation of the Retrospective Interview Technique, semi-structured interviews were conducted with women ( N = 30) ages 25 to 45 in order to identify turning points related to changes in closeness in significant same-sex friendships during adulthood. Results suggest that turning points and social support are closely linked in terms of their impact on closeness in female friendships. Overall, findings contribute to an understanding of why closeness levels fluctuate between female friends during the adult years.